MicroRNAs in endometriosis: biological function and emerging biomarker candidates†. Issue 5 (4th February 2019) - Bjorkman, Sarah; Taylor, Hugh S
Abstract: MicroRNAs (miRNAs), a class of small noncoding RNA molecules, have been recognized as key post-transcriptional regulators associated with a multitude of human diseases. Global expression profiling studies have uncovered hundreds of miRNAs that are dysregulated in several diseases, and yielded many candidate biomarkers. This review will focus on miRNAs in endometriosis, a common chronic disease affecting nearly 10% of reproductive-aged women, which can cause pelvic pain, infertility, and a myriad of other symptoms. Endometriosis has delayed time to diagnosis when compared to other chronic diseases, as there is no current accurate, easily accessible, and noninvasive tool for diagnosis. Specific miRNAs have been identified as potential biomarkers for this disease in multiple studies. These and other miRNAs have been linked to target genes and functional pathways in disease-specific pathophysiology. Highlighting investigations into the roles of tissue and circulating miRNAs in endometriosis, published through June 2018, this review summarizes new connections between miRNA expression and the pathophysiology of endometriosis, including impacts on fertility. Future applications of miRNA biomarkers for precision medicine in diagnosing and managing endometriosis treatment are also discussed. Abstract : MicroRNAs exhibit altered abundance in women with endometriosis, are involved in the pathophysiology of the disease, and represent promising biomarkers.